2000
DOI: 10.1524/ract.2000.88.9-11.603
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Ca2+/UO2 2+/CO3 2- complex formation at different ionic strengths

Abstract: Fluorescence spectroscopy was used to study the Ca 2+ /UO 2 2+ /CO 3 2− solution system at different ionic strengths. Fluorescent titrations confirmed formation of Ca 2 UO 2 (CO 3 ) 3 complex for which the values of log β 213 were measured at 0.1, 0.3, 0.7, 1.0 and 3.0 m (NaClO 4 ) at pcH = 8.1. Specific Interaction Theory (SIT) was used to correlate the log β 213 values as a function of ionic strength. The value obtained for log β 0 213 (I = 0) was 29.8 ± 0.7, indicating that Ca 2 UO 2 (CO 3 ) 3 was the predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 4 publications
6
99
1
Order By: Relevance
“…Uranium speciation is important in the safety assessment of nuclear waste repositories to predict actinide migration from such sites [24]. According to Clark et al [25], actinide elements released to the environment will eventually come into contact with water, containing phosphate and/or hydrogen phosphate anions which are exceptionally strong complexing agents for actinide ions inclusive uranyl, (UO 2 )…”
mentioning
confidence: 99%
“…Uranium speciation is important in the safety assessment of nuclear waste repositories to predict actinide migration from such sites [24]. According to Clark et al [25], actinide elements released to the environment will eventually come into contact with water, containing phosphate and/or hydrogen phosphate anions which are exceptionally strong complexing agents for actinide ions inclusive uranyl, (UO 2 )…”
mentioning
confidence: 99%
“…For example, Gudavalli et al (2013) showed that during dissolution of Na-and Ca-autunite, buffered bicarbonate solutions were undersaturated thermodynamically with respect to becquerelite, and uranyl carbonate and Ca-uranyl carbonate complexes were the predominant aqueous species, which were postulated to control mineral dissolution. Uranyl carbonate and alkaline-earth uranyl carbonate complexes are highly soluble and stable species that dominate the uranyl aqueous speciation between pH 7 and 11 (Bernhard et al, 1996;Kalmykov and Choppin, 2000;Bernhard et al, 2001) and also uranyl adsorption onto sediment and soils (Stewart et al, 2010). Indeed, breakthrough of U(VI) was noticeably retarded by sorption to quartz in control columns with low carbonate BPW compared to high carbonate BPW systems (Control 2, Fig.…”
Section: Effect Of Dissolved Carbonate On Dissolution Mechanismmentioning
confidence: 98%
“…Oxidation states of U within the soil were measured within columns (days 117 and 356) by synchrotron micro-X-ray absorption near edge structure (µ-XANES) spectroscopy 15 . In order to determine the aqueous uranyl species within column effluents, fluorescence spectroscopic and lifetime measurements were conducted 5,16 . Bacterial community dynamics during U-reduction and reoxidation processes were monitored by using both terminal restriction fragment length polymorphism (TRFLP) and high density oligonucleotide array 17 analyses.…”
mentioning
confidence: 99%
“…Calcium from calcite dissolution is effective in releasing U(VI) into solution through formation of Ca 2 UO 2 (CO 3 ) 3 complexes at near-neutral pH 5,16 (Eqs 4-5 in Table 3), which are much less susceptible to bioreduction 20 and sorption 21 . Although the magnitude of Ca 2 UO 2 (CO 3 ) 3 stability is currently unsettled 22 , it is acknowledged that neutral uranyl carbonate complexes with cations are important, and that the reported equilibrium constants 5,16 are useful for guidance. Dissolved Ca concentrations in column effluents were about 1 mM, indicative of equilibrium with calcite.…”
mentioning
confidence: 99%